Receptores B2 e B1 de cininas sensibilizam os receptores de potencial transitório anquirina 1 e vanilóide 4 contribuindo para os sintomas de dor musculoesquelética induzidos pelo anastrozol - Fialho, Maria Fernanda Pessano (2024)
Anastrozole, an aromatase inhibitor (AI), induces painful musculoskeletal symptoms, which reduce patients’ quality of life and may lead to therapy discontinuation. Studies have been made to understand the mechanisms involved in these painful symptoms to manage them better. In this sense, the Transient Receptor Potential Ankyrin 1 (TRPA1) and kinin B2 (B2R) and B1 (B1R) receptors contribute to the development and maintenance of painful symptoms associated with AI use. Another potential target that might be involved in the painful symptoms is Transient Receptor Potential Vanilloid 4 (TRPV4), which is co-localized with the TRPA1 channel in primary sensory neurons. However, the involvement of TRPV4 and the possible sensitization of TRPA1 and TRPV4 by signalling pathways downstream of B2R and B1R activation in anastrozole-induced pain are unknown. The musculoskeletal pain model was induced by oral administration of anastrozole in male C57BL/6 mice. Anastrozole caused pain symptoms (mechanical allodynia and loss of muscle strength) in mice, which were reduced by B2R (Icatibant), B1R (DALBk) or TRPA1 (A967079) antagonists. The local administration of B2R (bradykinin), B1R (DABk) or TRPA1 (AITC) agonists (all in sub-nociceptive doses) induced overt nociceptive behaviour and enhanced and prolonged the painful parameters in anastrozole-treated mice, which were attenuated after pre-treatment with their respective antagonists. Utilizing agonists, antagonists of these receptors, and an in vivo desensitization protocol, we confirmed the interaction between B2R, B1R, and TRPA1 in the painful symptoms induced by anastrozol. The local administration of PLC, PKC or PKA inhibitors attenuated the painful symptoms induced by B2R, B1R or TRPA1 agonists in animals previously treated with anastrozole. HC067047, TRPV4 antagonist, reduced the anastrozole-induced mechanical allodynia and muscle strength loss. In animals previously treated with anastrozole, the local administration of the TRPV4 (4α-PDD or hypotonic solution), B2R (bradykinin) or B1R (DABk) agonists (all in sub-nociceptive doses) enhanced the anastrozole-induced pain behaviours, which were reduced by pre-treatment with TRPV4 antagonist. Local inhibition of signalling pathways dependent on kinin receptor activation, PLC, PKC, or PKCε pathways attenuated the painful parameters induced by TRPV4, B2R and B1R agonists in animals previously treated with anastrozole. In this way, we confirmed the involvement of TRPV4, as well as the intracellular interaction of kinin receptors (B2R and B1R) with TRPA1 (via PLC/PKC and PKA signalling) and TRPV4 (via PLC, PKC and PKCε signalling). Thus, regulating kinin receptors or the TRPA1 or TRPV4 encourages targeted treatment to mitigate the potential impact of painful symptoms reported by AI users, such as anastrozole.